Risk factors of immature retina on the first screening for retinopathy of prematurity - Wedi Iskandar Kartamihardja; Gilang Mutiara; Yanuar Zulkifli Harun; Maulya Listrianti; Bestari Yuniah; Mayasari Kuntoyo (Paediatrica Indonesiana, 2023)
Background Immature retina is characterized by peripheral retinal avascularity. Retinal development is influenced by risk factors that affect retinal maturity. Objective To identify risk factors for immature retina on the first retinopathy of prematurity (ROP) screening at the Neonatology Care Unit, Al-Islam Hospital, Bandung, in 2013-2021. Methods This case-control, retrospective, observational study was performed by evaluating medical records of preterm infants screened for ROP. The subjects were divided into two groups, immature retina and mature retina. We recorded potential risk factors including gestational age (GA), birth weight (BW), birth weight for gestational age, respiratory distress syndrome (RDS), oxygen therapy >7 days, asphyxia, sepsis, multiple transfusion, apnea of prematurity (AOP), patent ductus arteriosus (PDA), and bronchopulmonary dysplasia (BPD) and analyzed them for potential associations with retinal development. Results On the first ROP screening of 203 premature infants, 5 (2.5%) had ROP, 90 (44.6%) had immature retinas, and 107 (53.0%) had mature retinas. Bivariate logistic regression analysis showed significant relationships between immature retina (P<0.05), GA (OR=0.575; P=0.000), BW (OR=0.997; P=<0.001), gestational age maturity (OR=2.639; P=0.006), RDS (OR=1.809; P=0.042), oxygen therapy of >7 days (OR=4.494; P=0.002), sepsis (OR=2.028; P=0.034), multiple transfusions (OR=4.656; P=0.000), AOP (OR=2.553; P=0.002), PDA (OR=2.119; P=0.030). Multivariate regression analysis revealed a significant simultaneous relationship between all the risk factors and immature retina, with a NÃ¤gelkerke R2 value of 0.421. Conclusion GA, BW, gestational age maturity, oxygen therapy of >7 days, sepsis, multiple transfusions, AOP, and PDA are significant risk factors of immature retina, be it independently or simultaneously.